Avant-Garde Canadian Literature : The Early Manifestations - Betts, Gregory, 1975- (Book collections on Project MUSE., 2013)
Avant-Garde Canadian Literature offers an entrance into the vocabulary of the ongoing and primarily international debate surrounding the idea of avant-gardism, providing readers with a functional vocabulary for discussing some of the most hermetic and yet energetic literature ever produced in this country.